GRAPHIC ORGANIZER: A LEARNING TOOL IN TEACHING PHYSICAL SCIENCE - Tandog, Virginia O; Bucayong, Cecilia O (PEOPLE: International Journal of Social Sciences, 2019)
The integration of the effective study techniques could still be a relevant education research topic if we are to consider the changing demand for skills brought about by technological advancements. Thus, Graphic Organizer as a teaching tool was developed and implemented to promote conceptual understanding in the solution processes of algorithmic related topics in Physical Science. Specifically, the study determined the level of academic achievement of the participants in the pretest and posttest assessment of a quasi-experimental research design. Further, this study also determined which group (control or experimental) performed better after applying the intervention. Results showed that the control and experimental groups pretest scores do not meet expected proficiency level, however, there was a significant improvement in their posttests scores described respectively as satisfactory and very satisfactory. It was found out further that participants from experimental group achieved significantly better than the participants from the control group. As observed, the participants have confidently and actively indulged themselves in graphic organizer guided activities resulting to a deeper understanding of concepts, retention, and mastery of contents.